Political challenges to developing non-traditional exports in Ghana: The case of horticulture exports - Lindsay Whitfield (Danish Institute for International Studies (DIIS), 2011)
The nascent Ghanaian horticulture export sector, which emerged in the mid-1980s, has been ignored by ruling elites, especially after the return to multiparty democracy in 1993. Ruling elites across the two party governments between 1993 and 2008 did not actively pursue initiatives to support the industry. Without sustained political support, the types of public-private coordination of actions and investments needed to help the sector expand and upgrade were not forthcoming in an effective and timely manner. This private sector-driven non-traditional export sector constitutes a neglected opportunity for export diversification and building a new agro-industry, and also highlights some of the factors explaining why the country's economy was still dependent on the traditional exports of cocoa and gold by the close of the 2000s. The political challenges to changing the productive structure in Ghana can be found in the characteristics of ruling coalitions - vulnerability of the ruling elite in power, the high fragmentation within ruling coalitions, and their existing sources of and strategies for financing the state and the ruling coalition, combined with the country's existing economic structure as well as the size and capabilities of domestic capitalists. The characteristics of ruling coalitions in Ghana shaped the incentives facing ruling elites such that the ruling elites were not sufficiently compelled to support new productive sectors, such as horticulture export, which did not (yet) provide substantial revenues.
Keywords: 330; Außenwirtschaftsförderung; Gartenbau; Obst; Regierungskoalition; Ghana